Pancreatic Cystosis in Two Adolescents with Cystic Fibrosis - Elpis Hatziagorou; Asterios Kampouras; Maria Sidiropoulou; Andreas Markou; Athanasia Anastasiou; John Tsanakas (Case Reports in Pediatrics)
We present pancreatic cystosis in two adolescents with cystic fibrosis, a 13-year-old girl and an 18-year-old boy. In pancreatic cystosis, which is a rare manifestation of CF, the pancreatic parenchyma is replaced with multiple cysts of different sizes. Pancreatic cystosis is mainly an imaging based diagnosis and frequent follow-up should be recommended.